FeOOH and Mn8O10Cl3 modified zeolites for As(V) removal in aqueous medium. Issue 8 (24th April 2017) - Krauklis, Andrejs; Ozola, Ruta; Burlakovs, Juris; Rugele, Kristine; Kirillov, Kirill; Trubaca‐Boginska, Anna; Rubenis, Kristaps; Stepanova, Valentina; Klavins, Maris
Abstract: BACKGROUND: Arsenic in drinking water poses serious potential health risks in more than 30 countries with total affected population of around 100 million people. The present study is devoted to the development of innovative sorbents based on zeolite materials for As(V) sorption by modifying raw materials with iron oxyhydroxide and manganese oxychloride. Natural clinoptilolite and synthetic zeolite A were modified in order to obtain improved sorption of As(V). Sorption properties of newly developed sorbents were studied. Zeolites containing natural clinoptilolite are chosen due to relatively low cost and their broad use in industrial production as well as characteristic large surface area. RESULTS: Results obtained indicate that modification of zeolites with FeOOH and Mn8 O10 Cl3 significantly improves the As(V) sorption capacity of newly developed materials. As(V) sorption on FeOOH‐modified aluminosilicates follows the Langmuir model, while on unmodified aluminosilicates it is described by the Freundlich model. As(V) sorption kinetics on both modified and unmodified materials most precisely can be described by Lagergren's pseudo‐second‐order kinetic model. Elevated As(V) concentration on the surface of Mn8 O10 Cl3 crystals and amorphous FeOOH indicates these compounds as responsible for sorption increase. CONCLUSION: Developed sorbents show improved performance in comparison with their unmodified counterparts, with a dramatic increase in As(V) sorption capacity up to 99.3 times in the case of FeOOH‐modified calcium zeolite A. These materials have great potential for As(V) removal in aqueous medium. © 2017 Society of Chemical Industry